Исследование сущности деловой репутации предприятия - Лазукина, А.О.; Сулыма, А.И. (Культура народов Причерноморья, 2014)
В данной статье рассматривается проблема деловой репутации предприятия, которая
играет важную роль в обеспечении надежности его деятельности. На основании имеющихся в
различных сферах деятельности теоретических подходов исследовано содержание деловой репутации.
Выделены ключевые элементы в определении деловой репутации. Определены отличительные черты
понятия "деловая репутация", которые позволят идентифицировать его среди схожих понятий.
Разработано авторское определение деловой репутации предприятия. Выявлена практическая ценность
положительной репутации предприятия. У даній статті розглядається проблема ділової репутації підприємства, яка відіграє
важливу роль у забезпеченні надійності його діяльності. На підставі наявних у різних сферах діяльності
теоретичних підходів досліджено зміст ділової репутації. Виокремлено ключові елементи у визначенні
ділової репутації. Визначено відмінні риси поняття "ділова репутація", які дозволять ідентифікувати
його серед схожих понять. Розроблено авторське визначення ділової репутації підприємства. Виявлено
практичну цінність позитивної репутації підприємства. The problem of business reputation of enterprise is examined in this article. Business reputation has
an important role in providing reliability of the enterprise. On the basis of present theoretical approaches are
investigated the content of of business reputation. The business reputation has been determined as ambiguous
and multifaceted concept, containing the economic, social, financial and other aspects. Key elements have been
distinguished in determination of business reputation. The distinctive features of the concept of «business
reputation» have been determined, that will allow to identify him among similar concepts. The author's
definition of business reputation of the enterprise has been developed. The practical value of positive reputation
of enterprise has been revealed. It has been determined that positive business reputation is often crucial for the
survival of enterprise in a competitive environment. The loss of business reputation can lead to significant
material costs and even to liquidation of enterprise. The positive business reputation is an important tool for
ensuring the reliability of the enterprise. Business reputation provides the certain level of trust to the enterprise
in society. The high level of trust to the enterprise in society allows to get additional incomes and benefits, those
straight influences on reliability of activity of enterprise and leads to its prosperity.